Dinâmica de grupo e método psicogenético aliados à metodologia ativa gv/go: na perspectiva dos professores do ensino fundamental - Santos, Vladiana Costa dos (2024)
One of the challenges facing teachers today is to get students interested in classes with more enthusiasm and autonomy. With the advancement of digital technologies, new ways of teaching and learning have been used for better learning, through active methodologies that develop students' creativity, criticality and cooperation. The question that guides this study arises: - Do Group Dynamics and Lauro de Oliveira Lima's Psychogenetic Method, combined with the GV/GO Active Methodology in the early years of Elementary School, contribute to improving teaching and learning processes? The aim is to analyze Group Dynamics in the light of Lauro de Oliveira Lima's Psychogenetic Method, focusing on the GV/GO Active Methodology from the perspective of teachers who work in the early years of Elementary School, under this vision. This is research of a basic nature, with a qualitative approach, based on bibliographical research and on-site investigations. The research collaborators are the teachers who work in the early years of Elementary School at Escola Nova, and experience Group Dynamics and the Psychogenetic Method, as a teaching method, as well as the school director, who has a pedagogical guidance role. To this end, research techniques and tools are used: bibliographic review, on-site observation, online semi-structured interviews, databases of national and international impact, such as Capes journals. In the field study, visits were made to the school, and observations took place in the context of classes and recreation. To treat the collected data, we used the sampling criterion by theoretical saturation and we used the content analysis technique in qualitative research, under the theory developed by Bardin (1977, 2016). The results, based on the data collected, indicate that teachers are aware of the relevance of the method, they understand that when they add methodological and theoretical knowledge to practices, students tend to become more engaged and demonstrate greater involvement in activities, resulting in more significant learning. . In the search for this new way of teaching and learning, this study is considered relevant, as the Psychogenetic Method of Lauro de Oliveira Lima, combined with the GV/GO Active Methodology, collaborate so that students and teachers in the teaching and learning processes become protagonists and developers of their own knowledge.